2021
DOI: 10.1126/sciadv.abe7953
|View full text |Cite
|
Sign up to set email alerts
|

High-performance combinatorial optimization based on classical mechanics

Abstract: Quickly obtaining optimal solutions of combinatorial optimization problems has tremendous value but is extremely difficult. Thus, various kinds of machines specially designed for combinatorial optimization have recently been proposed and developed. Toward the realization of higher-performance machines, here, we propose an algorithm based on classical mechanics, which is obtained by modifying a previously proposed algorithm called simulated bifurcation. Our proposed algorithm allows us to achieve not only high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
150
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(153 citation statements)
references
References 61 publications
3
150
0
Order By: Relevance
“…More recently, the same team proposed a modified SB algorithm (47), with which a fully connected 100,000-node graph with 10-bit weight resolution was solved. They showed that it can improve the solution accuracy and calculation time compared with the previous SB algorithm (46).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the same team proposed a modified SB algorithm (47), with which a fully connected 100,000-node graph with 10-bit weight resolution was solved. They showed that it can improve the solution accuracy and calculation time compared with the previous SB algorithm (46).…”
Section: Discussionmentioning
confidence: 99%
“…For large-scale problem sizes, D-Wave's new Leap Hybrid service [47], [48] is capable of processing up to 20,000 QUBO variables with fully connected graphs, using an approach of problem partitioning. Digital annealing technologies [49]- [52] also pave the way towards time sensitive optimization scenarios with high-parallelism and highperformance dedicated architectures.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is also observed in the SBM. [27,29] Whether or not CIM-SFC utilizes chaotic dynamics, however, is beyond the scope of this paper; to answer this question, we would need to further analyze how the parameters of CIM-SFC affect its dynamics and gain a deeper understanding of how CIM-SFC finds ground states.…”
Section: Numerical Simulation Of Cim-cac Cim-cfc and Cim-sfcmentioning
confidence: 99%
“…[25] Similarly, a network of dissipation-less quantum oscillators with adiabatic Hamiltonian modulation that can be described using a set of N deterministic equations can also be used to implement a heuristic algorithm on a modern digital platform. [27][28][29] Such heuristic algorithms are called simulated bifurcation machines (SBMs), [27,29] and a variant SBM will be studied in Section 6. Although the original SBM was inspired by dissipation-less adiabatic quantum computation, the version of SBM discussed in this paper (dSBM) is not a true unitary system, as dissipation is artificially added using inelastic walls to improve the performance of the algorithm.…”
mentioning
confidence: 99%